Researching Indices of Reliability of Navigation Parameters Meters Checking - Sushchenko , Olha; Saluyk , Olexander; Yehorov, Serhii (Electronics and Control Systems, 2023)
The article deals with the studying process of measuring navigation parameters by means of gyroscopic measurements instruments. The topic of research is connected with studying reliability of checking of gyroscopic measuring instruments. The instrumental and methodical components of the check’s reliability are determined. Probabilities of arising both false and indefinite failures are obtained. The relationship, which connects accuracy performances and mass-dimension characteristics, is represented. Graphical dependences, which characterize interconnection between the instrumental component of the check’s reliability with accuracy characteristics of navigation measuring instruments, are given. Graphical dependences, which illustrate change of the methodical component for different types of checks, are shown. The analysis of instrumental and methodical components of the reliability of checking is carried out. The obtained results can be useful for grounded assignment of tolerances on measured navigation parameters.